Integrating the ARCS Model with Instruction for Enhanced Learning - Arora, Amarpreet Singh; Sharma, Archana (Journal of Engineering Education Transformations, 2019)
This paper provides an overview of Keller's ARCS Model of Motivational Design and explores two case studies of the faculty integrating the model into their teaching practices for improving student motivation during the classroom sessions. Case studies described how instruction in the traditional classroom can be structured in order to improve student motivation and attention span. Findings of the studies indicated ARCS as a valuable tool for improving student engagement for a particular topic taught or instruction delivered. It works well alongside principles and techniques of instructional design. This paper fills a gap in literature on practical applications of motivational design in regular instruction and suggests best practices for teaching and assessment using the ARCS Model for Motivational Design.